The contrasting origins of glauconite in the shallow marine environment highlight this mineral as a marker of paleoenvironmental conditions - Tribovillard, Nicolas; Bout-Roumazeilles, Viviane; Abraham, Romain; Ventalon, Sandra; Delattre, Marion; Baudin, François (Comptes Rendus. Géoscience)
Glauconite is an authigenic mineral reputed to form during long-lasting contact between a nucleus (a pre-existing phyllosilicate) and seawater. This protracted contact makes it possible to subtract the ions necessary for the construction of the neoformed phyllosilicate, here, glauconite (a mineral very close to an illite, rich in K and Fe). As a result, glauconite is often associated with sediments deposited in a transgressive context with a strong slowdown in the rate of sedimentation and a relatively large water layer thickness. This is the case of the Cenomanian chalk of Boulonnais (north of France). Being chemically and physically resistant, glauconite is a mineral that is often reworked, like quartz grains. This is frequently the case of the Jurassic deposits of the Boulonnais, where glauconite, almost ubiquitous, either in traces or in significant proportions of the sediments, presents a grain size sorting attesting to its transport and reworking. However, these Jurassic deposits are shallow (shoreface, upper offshore), which supports the idea that the “glauconite factory” was itself in the shallow areas of the Boulonnais. The only identified Jurassic facies of the Boulonnais where glauconite is both relatively abundant, large in size and unsorted (non reworked) are oyster reefs that formed at the outlet of cold seeps linked to a late-Jurassic synsedimentary tectonic (Kimmeridgian, Tithonian). Our work makes it possible to hypothesize that isolated oyster reefs were environments combining the redox conditions and in contact with seawater favoring the authigenic formation of glauconite. The weakly reducing conditions necessary for the formation of glauconite here are attested by the contents of metallic trace elements sensitive to redox conditions (vanadium, germanium, arsenic, in this case). Our work thus adds a new element to the understanding of the mechanisms of formation of glauconite in shallow environments.